PELAKSANAAN DAN PENGAWASAN IZIN PERUNTUKAN PENGGUNAAN TANAH UNTUK PERUMAHAN DI KOTA DENPASAR - Jaya Winangun, I Gede Bagus; Wairocana, I Gusti Ngurah; Sudiarta, I Ketut (Kertha Negara : Journal Ilmu Hukum, 2013)
The implementation and monitoring land use allocation permit is to regulateactivities that occured in the city of Denpasar. Therefore this article will explain wheter thepermit alloment of land for residential use in Denpasar have been implemented andwhether the supporting factors and obstacles in the implementation and monitoring of landuse designation permit in Denpasar. The method which is used is emperical legal research.Te result of the research is the implementation and the monitoring of land use allocationpermits and it is influenced by supporting and inhibiting factors. In the settlement of theland use allocation permit done by applying the local regulation of Denpasar City Number6 year 2005 cconcerning the retribution for the land use allocation permit.
Keywords: Monitoring, Permit, Land use allocation, Denpasar City